ON GRID SOLAR POWER PLANT (SOLAR HOME SYSTEM) HOUSEHOLD SCALE - Alfian Ady Saputra; Sunaryo; Pungkas Prayitno; Riyan Ariyansah (Nacreva Publisher, 2023)
The need for electricity in Indonesia continues to increase every year and its supply is increasingly limited because most power plants in Indonesia still depend on conventional energy (fossil fuels). Solar power plants (PLTS) are very suitable to be developed in Indonesia because they have abundant sources of solar energy. with an average solar radiation intensity of about 4.8 kWh/m² per day. Therefore, in this study a design of a household-scale solar power plant (Solar Home System) will be made, with the aim of saving electricity and electricity bills from PLN. The power designed in this study is 0.9 kW. Using 3 units of ST Solar 300 Wp solar panels and the Solis On-Grid Mini-1000-4G Inverter. Based on the economic analysis, this design requires an initial capital of Rp. 17,500,000. savings in electricity bills obtained each month is IDR 154,464. and from the results of the BEP calculations that have been carried out, it is known that the capital will return in the 9th month-6th year